Immunoglobulins M and G to varicella-zoster virus measured by solid-phase radioimmunoassay: antibody responses to varicella and herpes zoster infections. - Arvin, A M (J Clin Microbiol, 1980)
Both immunoglobulin M (IgM) and IgG antibodies to varicella-zoster virus (VZV) were detectable in a solid-phase radioimmunoassay with 125I-labeled goat antisera to human immunoglobulins. Primary infection with VZV was associated with early production of IgM and IgG antibodies and rapid development of lymphocyte transformation to VZV antigen. Among eight subjects with varicella tested 1 to 4 days after onset, seven patients had IgG and six patients had IgM antibodies; all patients had both IgG and IgM antibodies within 7 days. An IgM response was documented by radioimmunoassay in 18 of 26 patients with herpes zoster. VZV antibodies could be assayed by radioimmunoassay in unfractionated serum with commercial goat antisera to human immunoglobulins and commercial VZV antigen. VZV-specific IgG binding was present in all sera from 42 subjects with a VZB antibody titer of greater than or equal to 1:8 as determined by indirect immunofluorescence and cellular immunity to VZV as determined by lymphocyte transformation and who had had varicella at least 20 years before testing. The geometric mean titer was 1:6,309, and titers were greater than or equal to 1:16,384 in 20 subjects. Antibody was present as determined by radioimmunoassay in 14 samples negative by complement fixation and in five samples negative by complement fixation and immune adherence hemagglutination. No specific binding was observed in 21 sera from subjects who were not immune to VZV as determined by indirect immunofluorescence or lymphocyte transformation despite the presence of herpes simplex or cytomegalovirus antibody indicated by complement fixation in 15 sera. High titers of VZV IgM antibody were detected in unfractionated sera despite the presence of high titers of VZV IgG antibody. The VZV radioimmunoassay provided a sensitive and practical method for measuring VZV IgG and IgM antibodies.